Thermal Bioclimate for Tourism: Case Study of Kuta, Bali Province, Indonesia - Nyoman Sugiartha; Andreas Matzarakis (Bandar Lampung University (UBL), 2014)
Weather and climate are influencing factors for tourism. Tourism destinations often require information about the weather and climate to assess their climate potential. In this regard, study on thermal bioclimate, i.e. human thermal comfort is essential. This study has assessed tourist thermal comfort perceptions and adaptation in Kuta, Bali Province of Indonesia, by applying physiologically equivalent temperature (PET) and thermal perception classifications (TPCs) for temperate and sub(tropical) regions. Analytical calculation of PET utilized RayMan model and synoptic meteorological data covering the period 2002-2012. The results show that frequencies of thermal comfort during whole day (02:00-23:00) for tourists from temperate region are higher than those for tourists from (sub)tropical region, indicating that tourism potential based on thermal comfort is high for those from the temperate region. However, around noon (11:00-17:00), thermal comfort of the tourists from (sub)tropical region is better (in which indicating more adaptable to the daytime climate conditions) than that of the tourists from the temperate region. In addition, it is shown that the months from June to September, particularly in July and August are the most suitable time to travel for the tourists from temperate region, whereas all year round is appropriate for those tourists from (sub)tropical region.